2021
DOI: 10.1158/0008-5472.can-21-0035
|View full text |Cite
|
Sign up to set email alerts
|

An Oncolytic Virus Expressing IL15/IL15Rα Combined with Off-the-Shelf EGFR-CAR NK Cells Targets Glioblastoma

Abstract: IL15 is a pleiotropic cytokine with multiple roles that improve immune responses to tumor cells. Oncolytic viruses (OV) specifically lyse tumors and activate immune responses. Systemic administration of IL15 or its complex with the IL15Rα and chimeric antigen receptor (CAR) natural killer (NK) cells are currently being tested in the clinic. Here, we generated a herpes simplex 1–based OV-expressing human IL15/IL15Rα sushi domain fusion protein (named OV-IL15C), as well as off-the-shelf EGFR-CAR NK cells, and st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 52 publications
0
79
0
Order By: Relevance
“…Our observation of unexpected toxicity begs for expanded study of novel ways to stimulate CAR-NK-cell cytokine receptor pathways while circumventing systemic cytokine delivery. Localization of IL-15 with membrane tethering 55 or targeted delivery through the use of oncolytic viruses 56 are alternative therapeutic strategies. Controllable cytokine expression using engineered inducible systems and safety switches also holds promise.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of unexpected toxicity begs for expanded study of novel ways to stimulate CAR-NK-cell cytokine receptor pathways while circumventing systemic cytokine delivery. Localization of IL-15 with membrane tethering 55 or targeted delivery through the use of oncolytic viruses 56 are alternative therapeutic strategies. Controllable cytokine expression using engineered inducible systems and safety switches also holds promise.…”
Section: Discussionmentioning
confidence: 99%
“…oHSV has proven to be relatively safe and has shown some activity in treating GBM 3 . In our previous studies, we found that oHSV treatment dramatically increased the intratumoral infiltration of immune cells [4][5][6][7][8][9] . However, tumor cells have evolved to engage the immune checkpoints, e.g., CD47 and PD-L1, and down-modulate the immune cells, thereby evading the antitumor immune response 10,11 .…”
mentioning
confidence: 89%
“…However, OV-IL15C, expressing an IL-15 super agonist (human IL-15/IL-15Rα complex), from OV-Q1 (HSV-1 γ34.5 and ICP6 deleted; rHsvQ1) was more effective at extending survival in a CT2A syngeneic mouse GBM model than OV-Q1, and this was associated with increased in NK and T cell infiltration [27]. The combination with intratumoral injection of human EGFR-CAR NK cells further significantly extended the survival of mice with CT2A-hEGFR brain tumors [27], representing a promising therapeutic strategy.…”
Section: Ohsv Armed With Il-15mentioning
confidence: 99%